Proses Pengelolaan Tenaga Pendidik dan Kependidikan Dalam Peningkatan Mutu Pendidikan Di SMPN 56 Surabaya - Felita, Almira Vashti; Ghorizah, Fithrotul; Windasari, Windasari; Hanivia Cindy, Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
The research was conducted at SMPN 56 Surabaya. The purpose of this study was to determine how the Management of Educators and Education Personnel at SMPN 56 Surabaya. This includes aspects of recruitment, professional development, performance appraisal. In addition, this study also aims to analyze the impact of the management of teaching and education personnel on student learning outcomes, the welfare of educators. This research is important because teaching and education personnel have a very important role in achieving the goals of quality education. Effective management can improve school performance and learning quality. Based on the research that has been done, it shows that effective management of teaching and education personnel contributes significantly to improving the quality of education, including the academic achievement of students. The form of this research is qualitative with an approach through interviews, observations and literature studies. The targeted outputs include an in-depth understanding of the policies and practices of managing teaching and education personnel at SMPN 56 Surabaya. management policies and practices at SMPN 56 Surabaya, recommendations for improvement, and contributions to improving the quality of education at SMPN 56 Surabaya. to improving the quality of education at SMPN 56 Surabaya.